Reading The Book of Jonah through the Eco-Spiritual Perspective - Liew, Hew Yan; Seach, Jin Beng; Pathinathan, Santini (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2023)
Whether one chooses to acknowledge or disregard its significance, nature has always been part of us. In an anthropogenic era, the dire state of the environment has made it an increasingly concerning topic of discussion among us. Nature has been extensively examined in numerous scholarly discussions ranging from secular to religious perspectives. This paper examines how nature plays a crucial role in helping us understand the relationship between God and humans, as portrayed in the Bible. The Bible being a religious text exists with very specific purposes. That being said, elements of nature were also used very specifically in the Bible. Most presently available scholarly research focuses on reading the significance of nature elements from religious perspectives. However, this research employs the eco-spirituality theory to examine the book of Jonah from the Bible to determine the relationship between Jonah, God, and nature. Through this secular perspective, the aim is to show that elements of nature have been carefully woven into narratives to signify various meanings. Furthermore, this research aims to identify how God communicates with humans through nature, which eventually helps to establish various forms of relationships between humans and nature. Through these newly formed relationships, we can understand the authority of a Creator and the consequences of obedience and submission. All these highlight the importance of co-existence between humans and nature, and examining the Bible through the lens of eco-spirituality perpetuates the relevance of the Bible to 21st-century readers.